Perceptions of volunteers on the effectiveness of Kenya Medical Training College-run free medical camps in enhancing access to healthcare by vulnerable communities - Ombasa, Zachary O.; Nyachae, Jonah R.; Mutiso, Urbanus; Mutiso, Raphael; Kwinga, Nicholas; Kaloki, Luciana; Musovya, James; Kinyae, Vincent; Nguutu, Gilbert K.; Nthei, Emma; Mwangi, Loise; Jonah, Luciah; et al. (International Journal Of Community Medicine And Public Health, 2024)
In certain regions of Kenya, such as Nyahururu, Kabarnet, Kasikeu, and Mbooni, inadequate access to healthcare services contributes to avoidable deaths. Organizations like the Kenya Medical Training College (KMTC) address this challenge by organizing free medical camps, involving both local and international volunteer healthcare workers. This study explored the effectiveness of KMTC's free medical camps through interviews with 18 key informants, including faculty, non-faculty members, and community leaders from purposefully sampled hardship areas, namely, Nyahururu, Kabarnet, Kasikeu, and Mbooni. The study found that KMTC's free clinics offered crucial services like curative care, immunization, maternal and child health services, disease sensitization, reproductive health services, and substance abuse education. However, limitations were identified, including a shortage of medications, lack of specialized screening, follow-up care, and referral services. Resources available included community health volunteers, KMTC and hospital staff, socio-structural support, and physical infrastructure. Challenges faced by volunteers included motivation issues, inadequate facilitation, limited stakeholder involvement in planning, and perceived service comprehensiveness issues. Despite these challenges, the community acknowledged the vital role of medical camps in delivering essential services to marginalized groups. Addressing resource shortages, enhancing stakeholder engagement, improving service comprehensiveness, and boosting volunteer motivation were highlighted as crucial steps to maximize community benefits.